Gender Inequality and its Implications on Economic Development of South Western Nigeria - Oluwaseun, Oyewale, Peter (International Journal of Publication and Social Studies, 2019)
Gender Inequality remains one of the many problems facing the African continent. Perhaps among the many spheres riddled with this problem is the economy of the continent which has been extensively affected. In Nigeria, particularly the South Western corner of the country occupied predominantly by the Yoruba, women have been observed to contribute immensely to the economy growth and social stability. Interestingly however, women in the region have been clothing others with the social and economic contributions while metaphorically remaining naked. This paper aims at making an assessment of this phenomenon and its overall implication to economic growth and development of the region. The methodology adopted for this work is historical approach. Hence, the study is based on primary and secondary sources. The primary sources comprise of oral interview, newspapers, government gazettes, while relevant books were consulted as useful secondary sources. The study concludes that gender inequality affects economic development of the region to a reasonable extent.